Analysis of the Spatial Equity of Sustainable Transport in the City of Curitiba, Paraná, Brazil - Paulo de Almeida Correia Junior; Ana Margarida Condeço-Melhorado; Cristina de Araújo Lima (Ambiente & Sociedade)
Abstract Equity in distribution of accessibility is directly related to quality of life and sustainability. Accessibility measures gain ground in studies on social exclusion, especially in cities, since most of the world’s population is urban. This study focuses on Curitiba, where a mobility solution has emerged - the BRT - implemented since 1974, but which presents rapid growth in the peripheries and a modal matrix based on unsustainable transport - mainly the automobile - whose infrastructure favors higher income groups. Thus, an attempt was made to investigate how the spatial variation of access to opportunities through public and pedestrian transport to essential services is configured, proposing a composite index of sustainable accessibility, in order to contribute to the analysis of equity in the distribution of access to opportunities and its relationship with socioeconomic characteristics. The composite and partial indexes show that the values are far below what could be considered an equitable distribution.